Natural Certainty Contract Dan DPK Terhadap Profitabilitas Melalui Non Performing Financing - Dwita Sandra Pratiwi; Mochamad Fariz Irianto; Supami Wahyu Setiyowati (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2022)
In an effort to increase profitability growth, it is necessary to pay attention to the factors that influence it, so that it can encourage Islamic banks to develop for the better. Type quantitative descriptive research. The research population is all BUS registered with OJK in 2015-2019 and a sample of 2 BUS obtained through purposive sampling method. Documentation technique used for data collection. The research results state that ijarah financing, istishna financing, and NPF has a negative and significant effect on ROA. NPF has no effect on ROA. Ijarah financing has no effect on the NPF. Istishna financing and NPF have an effect positive and significant on the NPF. Ijarah financing has no effect on ROA through NPF. Istishna financing and NPF have a negative and significant effect on ROA through NPF